2022
DOI: 10.3390/f13101553
|View full text |Cite
|
Sign up to set email alerts
|

Mechanized Wood Extraction: Impacts on Operators’ Hearing Health

Abstract: The activity of the mechanized extraction of wood, carried out by means of self-propelled forest machines, consists of moving the wood cut inside the forest stand from the planted forests to the roadside. During displacements, these machines normally travel over forest residues and stumps, which can demand greater motor power from the engine, in addition to the possible increase in occupational noise levels. In this context, we evaluated whether, when operating different self-propelled forest machines in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In skidding operations, for instance, changes in the magnitude of pre-skidding and skidding distances contribute to a change in the work elements' share in a work cycle [21], which also applies to cable yarding, as demonstrated by this study. Accounting for such a variation to characterize noise exposure is challenging if conventional studies are used, as it would necessitate measurements carried out to cover all the potential variations in operational factors, in addition to the type of machine used for extraction [29,30]. For sledge-based cable yarding, this is virtually impossible since it would involve using many resources in collecting and processing data, and previous work has shown that it is difficult to develop meaningful models which relate noise exposure to distance when conducting a study using this approach [21].…”
Section: Discussionmentioning
confidence: 99%
“…In skidding operations, for instance, changes in the magnitude of pre-skidding and skidding distances contribute to a change in the work elements' share in a work cycle [21], which also applies to cable yarding, as demonstrated by this study. Accounting for such a variation to characterize noise exposure is challenging if conventional studies are used, as it would necessitate measurements carried out to cover all the potential variations in operational factors, in addition to the type of machine used for extraction [29,30]. For sledge-based cable yarding, this is virtually impossible since it would involve using many resources in collecting and processing data, and previous work has shown that it is difficult to develop meaningful models which relate noise exposure to distance when conducting a study using this approach [21].…”
Section: Discussionmentioning
confidence: 99%
“…The most represented machines and tools were chainsaw (37), skidder (17), pre-harvesting tools (16), harvester (14), forwarder (12), and farm tractor (12). Overall, almost onethird of all records were noted in Brazilian articles (Figure A2) where the most records were observed for skidder (8), feller buncher (7), harvester (6), pre-harvesting tools (6), chainsaw (5), and forwarder (5). Out of 25 countries, chainsaw was noted in articles from 17 countries including Brazil and Croatia with five records, Poland and Romania with four, and Iran and Italy with three records each.…”
Section: Article Classificationmentioning
confidence: 99%
“…Of the European countries, Italy has the most publications (12). Other countries with five or more articles include Poland (8), Romania (7), and Croatia (5).…”
Section: Publishing Year Country Journal and Field Overviewmentioning
confidence: 99%
See 1 more Smart Citation